Formulation And Evaluation Of Clotrimazole And Ichthammol Ointment - G.RAJALAKSHMI; N. DAMODHARAN,; CHAUDHARY VIJAY KUMAR; VAGHAJI BHAI; POGAL JANARDHANREDDY R. (International Journal of Pharma and Bio Sciences, 2010)
We intended to develop a desired ointment for treatment of fungal infection like eczema itching, pruritis. Main objective of this study is to formulate the ointment with different ointment bases having good consistency, better diffusion, and antifungal and antiseptic properties. Combination of clotrimazole and ichthammol is good for treatment of infection caused by coryne bacteria and also used for skin infection as clotrimazole and ichthammol having antifungal and antiseptic properties respectively. To assess the efficacy of formulations assay, drug release, uniformity, viscosity, diffusivity, rheology, stability, spread ability, permeability and other physical characteristics were evaluated. Two Formulations, formulation A and B were prepared with same active ingredients except different bases. Formulation A contains white soft paraffin and cetostearyl alcohol while B contains hard paraffin, cetostearyl alcohol, Light liquid paraffin and microcrystalline wax. Formulation B was found better than formulation A in all aspects like spreadability, viscosity, consistency, stability, diffusibility etc.